Mingary in Ardnamurchan: a review of who could have built the castle - Petre, James Scott (Proceedings of the Society of Antiquaries of Scotland, 2015)
This short paper was prompted by the current interest in Mingary Castle, brought about by the major works recently undertaken there. It notes that its building has been attributed to various kin-groups by different scholars, the most recent and fullest analysis making a firm case for the MacDougalls. The paper reviews what evidence there is and concludes that there can be no absolute certainty on the matter.